The Story of the End of the World: An Alternative Approach to the Future at the Japanese Museum of Science and Innovation - Shea, Michael (The Unfamiliar, 2014)
The following discussion is a critical assessment of the “Story of the End of the World: 73 Questions We Must Answer”, an exhibition at the Miraikan. The Tohoku earthquake and tsunami on the 11th of March 2011 created the necessity for collective catharsis regarding various threats posed by the future. I will argue that the outcome of the exhibition differs significantly in content, presentation and meaning to the more conventional visions of the future presented elsewhere in the museum.